The cold ceramic material - Jalil Modaresi; Hamid Reza Hemati (Wolters Kluwer Medknow Publications, 2018)
The purpose of this paper was to review the composition, sealing ability, biocompatibility and various physical properties of cold ceramic (CC) material that potentially used as a root filling material. The review of the articles was performed by electronic and manual searching methods regarding the properties of CC from November 2000 to May 2016. The results revealed that there were many published reports carried out on the properties of CC. Only one article had extensively studied the composition of CC, five studies had investigated the sealing ability of CC, three articles had studied the biocompatibility, and some studies had investigated the radiopacity, setting time, pH value, and solubility of CC. It was concluded that CC material had good potential for endodontic use. Furthermore, clinical studies are needed in these areas.